2012
DOI: 10.3201/eid1803.111905
|View full text |Cite
|
Sign up to set email alerts
|

Novel Orthobunyavirus in Cattle, Europe, 2011

Abstract: In 2011, an unidentified disease in cattle was reported in Germany and the Netherlands. Clinical signs included fever, decreased milk production, and diarrhea. Metagenomic analysis identified a novel orthobunyavirus, which subsequently was isolated from blood of affected animals. Surveillance was initiated to test malformed newborn animals in the affected region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
670
0
29

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 596 publications
(715 citation statements)
references
References 7 publications
8
670
0
29
Order By: Relevance
“…The clinical signs of SBV infection in cattle can be increased body temperature, reduced milk yield and diarrhoea, and, like other members of this group, i.e. Akabane virus, the virus also infects the embryo or fetus of ruminants and can cause severe malformation (Bilk et al, 2012;Hoffmann et al, 2012;Wernike et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signs of SBV infection in cattle can be increased body temperature, reduced milk yield and diarrhoea, and, like other members of this group, i.e. Akabane virus, the virus also infects the embryo or fetus of ruminants and can cause severe malformation (Bilk et al, 2012;Hoffmann et al, 2012;Wernike et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks in northern Europe of bluetongue virus (Carpenter, 2009), and recently Schmallenberg virus (Hoffmann et al, 2012), have demonstrated the devastating effect of midge-borne viruses on naïve livestock populations. Subsequently, there has been increased concern over the risk of introduction of other midge-borne viruses, such as AHSV, and the need for evidence-based control strategies (Carpenter et al, 2008a(Carpenter et al, , 2009MacLachlan and Guthrie, 2010;Papadopoulos et al, 2010;Backer and Nodelijk, 2011;MacLachlan and Mayo, 2013;Napp et al, 2013;Robin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bluetongue (BT) and Schmallenberg diseases (SB) have been reported in northern Europe in recent years (Thiry et al, 2006;Hoffmann et al, 2012). BT is an infectious and non-contagious disease first described in South Africa (Anon., 1876), of which serotype 8 was detected for the first time in northern Europe in August 2006 (Thiry et al, 2006).…”
Section: Introductionmentioning
confidence: 99%